Unsupported Pt3Ni Aerogels as Corrosion Resistant PEFC Anode Catalysts under Gross Fuel Starvation Conditions. Issue 6 (1st January 2018) - Henning, Sebastian; Shimizu, Ryo; Herranz, Juan; Kühn, Laura; Eychmüller, Alexander; Uchida, Makoto; Kakinuma, Katsuyoshi; Schmidt, Thomas J.
Abstract : Mitigating catalyst corrosion is crucial for the commercial success of polymer electrolyte fuel cells (PEFCs). Novel catalysts that can withstand the harsh conditions in case of gross fuel (i.e. H2 ) starvation events at the PEFC anode are needed to increase the fuel cell stack's service life and to meet the durability targets set for automotive applications. To make progress in this respect, we have tested an unsupported, bimetallic Pt3 Ni alloy (aerogel) catalyst at the PEFC anode and subjected it to a stress test that mimics the high potentials (≥ 1.5 V vs. the reversible hydrogen electrode) encountered upon fuel starvation. In contrast to commercial carbon-supported platinum catalysts (Pt/C), the Pt3 Ni aerogel displays excellent durability and performance retention in end-of-life fuel cell polarization curves. Additionally, the aerogel catalyst shows ≈35% higher surface-specific activity for the hydrogen oxidation/evolution reaction than Pt/C. These results highlight the great potential of using novel unsupported catalysts at the anode of PEFCs.